Relationship of Earnings Quality and Segment Disclosure in Decreasing Cost of Equity - Siti Khomsatun; Sylvia Veronica Siregar; Sidharta Utama (University of Merdeka Malang, 2018)
Investors would analyze the reporting of segments disclosure in the notes to the financial statements, addition to the main reporting that presents earnings and cash flows. We investigated the relationship between the segment disclosure level and the earning quality that could decrease the cost of equity. Sample of this research were 242 firms-years of manufacture industry firms. This research used simultaneous test; the first stage was a regression of segment disclosure level on earning quality and the second stage was a regression on the cost of equity. Segment disclosure level was measured from PSAK 5 Operating Segment (2009); the cost of equity measured using industry-adjusted E/P Ratio; earning quality measured using absolute of accrual quality and absolute of abnormal accrual. We found that earnings quality positively influences on segment disclosure level. We proved that there was a complementary effect between them. The second result showed that the segment disclosure level decreases the cost of equity, but marginally. The third result proved that in the second order condition, the segment disclosure level was stronger in decreasing the cost of equity. We proved that there was endogeneity of segment disclosure level in decreasing cost of equity.JEL Classification: C34, D23, M14DOI: https://doi.org/10.26905/jkdp.v22i3.2304